Consumer Confidence in Mediating Fiscal and Monetary Policy Effects on Indonesia’s Markets - Shanti Pramelia; Herry Achmad Buchory (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study explores how consumer confidence mediates the effects of fiscal and monetary policies on Indonesia’s real investment and stock market performance. Fiscal and monetary policies are critical for economic stability, yet their effectiveness may depend on public sentiment, an area underexplored in emerging markets. The research aims to examine the mediating role of consumer confidence in these relationships, using quarterly data from 2000 to 2024 sourced from Indonesian Economic and Financial Statistics, Central Statistics Agency, and Indonesia Stock Exchange. A quantitative approach employs Principal Component Analysis to create composite policy indices, Vector Autoregressive models, Granger Causality tests, and Sobel tests to analyze direct and indirect effects. Findings reveal that fiscal and monetary policies significantly influence investment and stock markets, with consumer confidence strongly mediating monetary policy effects and moderately mediating fiscal policy impacts. These results highlight the psychological dimension of economic policy, emphasizing consumer sentiment’s role in enhancing policy outcomes. The study concludes that policymakers should integrate public sentiment into macroeconomic strategies to foster sustainable economic growth in Indonesia.